A would be the correct answer because the y variable only has a coefficient of 1. So we would solve for y, which would get us y=3x+5, then we would substitute the value in the second equation which would look like -4x+5(3x+5)=58. Hope this helpss. :)
That is true, I don,t quite know how to explain it but I just did this problem yesterday.
A) 4a - 3b + 2c
4(2, -1, 5) - 3(4, 3 , -2) + 2(5, 4, 0) = (8, -4, 20) - (12, 9, - 6) + (10, 8, 0) =
= (8 - 12 + 10 , -4 - 9 + 8 , 20 + 6 + 0) = (6, - 5, 26)
Answer: (6, - 5, 26)
b) magnitude of vector b
c) vector of length 7 parallel to vector c
=> m(5,4,0) = (5m,4m,0)
=>
=> m = 7 / √41 ≈ 1.093
=> 1.093 (5, 4, 0) = (5.465 , 4.372, 0)
Answer: (5.465 , 4.372 , 0)
Answer:
Step-by-step explanation: